Decision-making structures for successful management in Zimbabwe - Reinford Khumalo (South African Journal of Business Management, 1999)
This article discusses one of the management attributes discovered about Zimbabwe's most successful companies - decision-making structures. Seven most successful companies from among those quoted on the Zimbawean Stock Exchange (ZSE) were selected in terms of financial and macroeconomic criteria in their industrial categories. The research for attributes was mainly qualitative - consisting of interviews of chief executives, departmental managers, skilled, semi-skilled, and unskilled employees of the companies. The interviewees were also asked to complete a quantitative instrument, a semantic differential. Data from the interviews were content analysed. The findings showed that these companies have both centralised and decentralised decision-making structures that are in strata. The strata consist of those decisions that concern policy matters and are made at top management level and those at middle management level that take into account the input of the employees. This attribute has had some influence in the success of these companies and could thus contribute to the success of other less successful companies with a socio-economic situation similar to that of Zimbabwe's, the host country in which the study was conducted.
Keywords: 650